Ekonomi Sirkular dalam Pengelolaan Sampah Organik Menggunakan Lalat Tentara Hitam - Rizal Bahtiar; Kamelia Kamelia (Jurnal Ilmu Pertanian Indonesia, 2024)
The problem of organic waste can be solved by applying circular economy principles, namely in waste management using black soldier fly (BSF) maggots. These larvae can decompose organic waste into compost that can be used in agricultural activities. The results of adult larvae can be used as feed in livestock and fish because they contain high protein. The objectives of this study are (1) to identify the amount of organic waste absorption with BSF larval farming business, (2) to analyze the financial feasibility of cultivation in BSF Maggot Cultivation business units in Balaraja and in Tunas, (3) to analyze business efficiency in animal husbandry and fisheries through a circular economy system in the use of BSF larval feed. The research used descriptive-quantitative analysis, financial feasibility analysis, and business efficiency analysis. The results showed that the amount of waste absorption from larval farming business activities reached 430.7 tons/year, with the total land area needed for cultivation being 137,855 m2. The results of the business financial feasibility study show that the Tunas and Balaraja Units are feasible because they have met the eligibility criteria for NPV > 0, Net B/C > 1, IRR > interest rate, and PP > the life of the project. Business efficiency proves that fisheries and livestock business activities integrated into BSF larval cultivation are more efficient in spending on the cost of commercial feed used and provide higher profits in their businesses. Keywords: business efficiency, BSF, circular economy, financial feasibility, maggot black soldier fly, organic waste